EVALUASI INOVASI RASA TERHADAP PRODUK CEMILAN TRADISIONAL (STUDI KASUS PADA PT. SINUR RASYID SEJAHTERA DI KOTA MAKASSAR) - Ibrahim, Siti Nurul Rahmah Maulida; Nurliani, Nurliani; Rosada, Ida (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2025)
Entrepreneurship is a strategic means for students to develop their potential, practice independence, and apply their knowledge directly in the real world. Entrepreneurship not only serves as an alternative source of income but also as a medium for learning important skills such as leadership, decision making, and creativity. This study is motivated by the market potential in the traditional culinary sector, particularly traditional snacks, which still have a wide customer base in society. Additionally, this entrepreneurial initiative aims to empower local agricultural products such as peanuts and spices, which are easily obtainable from nearby farmers. The type of business developed involves production and marketing in three flavor variants—original, balado, and barbecue—with attractive and informative packaging to enhance competitiveness. The objectives of this activity are to create an independent and sustainable business, optimize the utilization of local raw materials, and contribute economically and socially to the surrounding community. The implementation of the activity was carried out through an entrepreneurship approach based on market research and product innovation. The results indicate a positive response from consumers toward the development of flavor variants. This entrepreneurial activity has the potential to grow as a model for local agribusiness-based enterprises that are not only profit-oriented but also promote sustainability and community empowerment.